Pacifying persephone, reawakening artemis: feminist archetypes in Hanna Alkaf’s The Weight of Our Sky (2019)/ Syazliyati Ibrahim and Mohamad Rashidi Mohd. Pakri - Ibrahim, Syazliyati; Mohd. Pakri, Mohamad Rashidi (Universiti Teknologi MARA, Perak, 2024)
Malaysian literature in English (MLE) is a relatively recent practice that stretches back to shortly after World War II and is primarily founded on the writings of college students. MLE then develops into a corpus of Anglophone writing that relates stories with unmistakably Malaysian experiences. By the same token, Malay women writers’ contributions to MLE are also rather slow to bloom despite its gradual increase. The knowledge of Malay women’s experiences has been primarily examined using feminist frameworks, granting this group of women agency and voice in MLE. However, most prior research on Malay women in MLE has only investigated women's conscious perception or their ego level. This research, contrastingly, seeks to demonstrate how the primordial images present in the collective unconscious of the main character may influence the main character’s reality. To achieve this, the feminist archetypal theories are applied to a contemporary MLE novel by Hanna Alkaf, focusing the discussion on two feminist archetypes, Persephone and Artemis. A close reading of the text to analyse the thoughts and actions of the protagonist was carried out, guided by the elements present in the archetypal representations of Persephone and Artemis. The results indicate that the protagonist of the fictional work may be predisposed to the feminist archetypes that are activated in her collective unconscious. The feminist archetypes simultaneously benefit the female character to work towards possible healing and individuation as well as helping her to deal with her psychological issues.